Jews and Non-Territorial Autonomy: Political Programmes and Historical Perspectives. Issue 1 (1st January 2016) - Gechtman, Roni
Abstract: Non-territorial autonomy, in various forms, was an enormously popular idea among Central and East European Jews in the early twentieth century, until two major events, the extermination of most European Jews during the Holocaust and the creation of the State of Israel as an ethnonational state in 1948, sidelined the public debate, among Jews, on alternatives to the nation state. This article analyses the relatively little known (but intellectually fecund) political programmes for Jewish autonomy in Europe in the first half of the twentieth century: the non-territorial Jewish autonomy envisioned by proponents of diaspora nationalism (primarily the historian Simon Dubnow), the national–cultural autonomy proposed by the Jewish Labour Bund (elaborated mainly by Bundist theorist Vladimir Medem) and the proposals by some liberal Zionists, such as Robert Weltsch and Hans Kohn, of Brit Shalom, to create a binational state in Palestine. It also considers the few historical attempts to implement these ideas in practice.